Incidence of Bone Cement Implantation Syndrome in Patients Undergoing Cemented Knee Replacement and Hip Arthroplasty Procedures - Rehman, Sami Ur; Rehman, Abdul; Rehman, Eesha; Razzaq, Aasim; Haider Ali, Syed Muhammad; Inayat, Maryam (Biological and Clinical Sciences Research Journal, 2025)
Bone Cement Implantation Syndrome (BCIS) is a potentially fatal perioperative complication characterized by hypoxia, hypotension, cardiac arrhythmias, and cardiac arrest. Reported incidences range from 28% to 37% globally. BCIS is classified by severity into Grade 1 (moderate hypoxia or hypotension), Grade 2 (severe hypoxia, severe hypotension, or unexpected loss of consciousness), and Grade 3 (cardiovascular collapse requiring cardiopulmonary resuscitation). Objective: To determine the incidence of Bone Cement Implantation Syndrome (BCIS), identify its severity grades, evaluate associated risk factors, and propose strategies to reduce morbidity and mortality in patients undergoing cemented hip and knee arthroplasty. Methods: This prospective cross-sectional study was conducted in the Orthopaedics Operation Theatres and the Department of Anaesthesia at Doctors Hospital and Medical Centre, Lahore, over six months, from September 2024 to February 2025, following approval from the College of Physicians and Surgeons, Pakistan. A total of 100 patients aged 20–80 years, classified as ASA I–IV, undergoing cemented total hip or knee arthroplasty under general, spinal, or combined spinal-epidural (CSE) anaesthesia were included through non-probability consecutive sampling. Patients with ASA >IV, chronic liver or kidney disease, acute kidney injury, carcinogenic states, or those refusing consent were excluded. The incidence and severity of BCIS were recorded intraoperatively based on established criteria. Data were analyzed using SPSS version 26, with descriptive statistics applied to determine incidence, distribution by anaesthesia type, and mortality rates. Results: Among 100 patients, 19 (19%) developed BCIS. Of these, 14 (73.6%) had Grade 1, 3 (15.6%) had Grade 2, and 2 (10%) had Grade 3 BCIS. The highest incidence occurred within 5–8 minutes after cementation. Regarding anaesthetic type, BCIS was observed in 5 (26.3%) patients under general anaesthesia, 8 (42.1%) under spinal anaesthesia, and 6 (31.5%) under combined spinal-epidural anaesthesia. Both Grade 3 cases occurred during hip arthroplasty in ASA-III patients, with a mortality rate of 100% in this group. Conclusion: Bone Cement Implantation Syndrome remains a critical cause of intraoperative morbidity and mortality in cemented arthroplasty procedures. Early recognition, vigilant perioperative monitoring, optimized pre-hydration, prophylactic use of low-dose epinephrine, and effective multidisciplinary coordination between surgical and anaesthetic teams can significantly reduce adverse outcomes.